Urban Public Transport Services in Selected Czech Towns - HORÁK, Jiří; KUKULIAČ, Pavel; KOLODZIEJ, Ondřej (GeoScience Engineering, 2023)
Urban public transportation systems in 26 selected Czech municipalities are studied using their timetables, location of stops, and price survey. The methodology of their processing is proposed. A set of indicators describing spatial accessibility, performance, and prices are analysed mainly for their relationships to the population with an indication of the municipalities which most deviate from common trends. A proposed four-dimensional evaluation system covers the spatial accessibility operationalised by the number of stops, the service frequency using the number of trips per route, the velocity for selected transport mode and the cost assessed by the price of a one-year ticket or equivalent. The results show the fare fees do not correspond to the performance of urban public transport. Keywords: Cluster analyses; Czechia; Public transport; Regression analyses; Time schedule; Urban transport.